Penerapan Model Contextual Teaching and Learning pada Materi Ragam Gejala Sosial untuk Meningkatkan Hasil Belajar Siswa - Sari Dewi, Lidya; Siddiq, Ilhamdi (Jurnal Pendidikan Tambusai, 2023)
Learning should be able to develop 21st century competencies, better known as 4C. Based on the problems found in the field, it shows that student learning outcomes in the aspects of knowledge and skills are low. The CTL model is a solution to this problem. The aim of this research is to investigate the effect of implementing the CTL model on student learning outcomes. This research method uses classroom action research or CAR. This CAR applies a cycle model consisting of planning, implementation, observation and reflection. The research instrument uses test questions to assess knowledge and performance assessment sheets to assess skills. The data analysis technique uses descriptive statistical analysis. From the results of data analysis, it can be stated that the application of the contextual teaching and learning model can improve student learning outcomes both in the knowledge and skills aspects. The implication of the results of this research is that teachers need to use context to motivate and construct student competence.